Drug-like Properties and Fraction Lipophilicity Index as a combined metric - Anna Tsantili-Kakoulidou; Vassilis Demopoulos (International Association of Physical Chemists (IAPC), 2021)
Fraction Lipophicity Index (FLI) has been developed as a composite drug-like metric combining logP and logD in a weighted manner. In the present study an extended data set confirmed the previously established drug-like FLI range 0-8 using two calculation systems for logP /logD assessment, the freeware MedChem Designer and ClogP. The dataset was split into two classes according to percentage of fraction absorbed (%FA) - class 1 including drugs with high to medium absorption levels and class 2 including poorly absorbed drugs. The FLI and FLI© (ClogP based FLI) drug-like range covers 93% and 90 % of class 1 drugs, respectively. The dependence of the degree of ionization to intrinsic lipophilicity within the FLI (FLI©) drug-like range as well as the inter-relation between the other Ro5 properties (Mw, HD, HA) was explored, so as to define drug-like / non drug-like combinations as a safer alternative to single properties for drug candidates' prioritization. In this sense we propose a combined metric of Mw and number of polar atoms (Mw/NO) to account for both size and polarity. Setting the value 50 as  cut off, a distinct differentiation between class 1 and class 2 drugs was obtained with Mw/NO>50 for more than 70% of class 1 drugs, while the opposite was observed for class 2 drugs.